Synthesis of Zeolite supported bimetallic catalyst and application in n-hexane hydro-isomerization using supercritical CO2. Issue 4 (August 2021) - Al-Rawi, Usama A.; Sher, Farooq; Hazafa, Abu; Bilal, Muhammad; Lima, Eder C.; Al-Shara, Nawar K.; Jubeen, Farhat; Shanshool, Jabir
Abstract: The loading of novel bi-and tri-metallic bifunctional catalysts such as Pt–Ru, Pt–Zr, and Pt–Ru–Zr over original zeolites (H-MOR and H-ZSM-5) and new cations modified zeolites (Sr-MOR, Ba-MOR, Sr-ZSM-5, and Ba-ZSM-5) by supercritical CO2 method are investigated for n-hexane isomerization. A fixed bed micro-reactor unit was used for catalytical hydro-isomerization of n-hexane at different temperature ranges (250–325 °C), H2 /HC ratios of 3, 6, and 9 mol and pressure of 5 bar. The chemical and physical properties of prepared zeolite nanoparticles were characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET), and thermogravimetric analysis (TGA). It is reported that the metal loaded in scCO2, results in more uniform and tiny metal nanoparticle (1.37 nm) dispersion with high stability and revealed that high loading pressure in scCO2 (280–300 bar) results in higher catalytic activity and surface area. H-MOR and H-ZSM-5 possess the maximum BET surface area of 539.21 and 403 m 2 /g and pore size of 90.73 and 105.06 Å respectively. The finding also revealed the maximum n-hexane conversion and selectively of about 99.10% and 32.23% for Pt–Ru/H-ZSM-5%, 93.55%, and 99.72% for Pt-Zr/H-ZSM-5, and 97% and 29.74% for Pt–Ru–Zr/H-MOR catalysts respectively at H2 /HC ratio of 9 and 250–325 °C. Moreover, Pt–Ru/H-ZSM-5, Pt–Zr/Ba-ZSM-5, and Pt–Ru–Zr/Ba-ZSM-5 showed the maximum yield of 11.5% and 17.7%, 40.58% and 33.19%, and 11.5% and 9.1% of 2-methyl-pentane (2-MP) and 3-methyl-pentane (3-MP) respectively at H2 /HC ratio 9 and 250–325 °C. Based on results, it is concluded that Pt–Zr catalyst over ZSM-5 showed better catalytical activity among all for n-hexane isomerization, while Pt–Ru and Pt–Ru–Zr demonstrated better hydrocracking reactions. Graphical Abstract: ga1 Highlights: n-Hexane hydro-isomerization was accomplished by bi-and tri-metallic catalysts loaded over zeolites by scCO2 method. For the first time, H-ZSM-5 and H-MOR zeolites were modified with barium and strontium cations. A maximum yield of 40.15% and 38.56% was reported for 2-MP and 3-MP respectively with Pt-Zr/Sr-ZSM-5 at 300 °C. Pt-Zr loaded over ZSM-5 (in both Ba and Sr forms) showed better n-hexane conversion and isomerization at 300 °C. ZSM-5 catalysts are the most selective that gave better selectivity, while MOR is more active for n-hexane conversion.